Schedules of lectures and Monte Carlo method - Grigorjev, Nikolaj; Stepanauskas, Gediminas (Lietuvos matematikos rinkinys, 2011)
In this paper the problem of the construction of schedule of lectures is considered. The Markov chain Monte Carlo method is used. A particular program based on simulated annealing algorithm was created.